2000
DOI: 10.1007/3-540-44447-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Spectroscopy and Excited State Dynamics of Rh(III) and Pd(II) Chelates as Studied by Optically Detected Magnetic Resonance Techniques

Abstract: In this paper we review optically detected magnetic resonance (ODMR) investigations of a series of Rh 3+ (4d 6 ) and Pd 2+ (4d 8 ) complexes in the lowest excited electron spin triplet state. Starting with a brief survey of the technique of optical detection of magnetic resonance, zerofield and low-magnetic field ODMR results are reviewed for the tris-diimine chelates [Rh(phen) n (bpy) 3-n ] 3+ , where phen = 1,10-phenanthroline, bpy = 2,2¢-bipyridine, and n = 0, 2, or 3, and for the mixed cyclometalated chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The optical high-resolution measurements were accomplished with experimental equipment 22 and an optical setup as specified previously. The ODMR spectrometer used was the same as also described elsewhere. , Optical excitation for these ODMR experiments was at 340 mm (∼29400 cm -1 ) using a 100 W high-pressure mercury lamp and an UG11 filter. ODMR spectra were recorded for the sample in a bath of liquid helium pumped down to 1.4 K. Small magnetic fields (up to 400 G) were applied by means of superconducting Helmholtz coils immersed in the liquid helium bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical high-resolution measurements were accomplished with experimental equipment 22 and an optical setup as specified previously. The ODMR spectrometer used was the same as also described elsewhere. , Optical excitation for these ODMR experiments was at 340 mm (∼29400 cm -1 ) using a 100 W high-pressure mercury lamp and an UG11 filter. ODMR spectra were recorded for the sample in a bath of liquid helium pumped down to 1.4 K. Small magnetic fields (up to 400 G) were applied by means of superconducting Helmholtz coils immersed in the liquid helium bath.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the small ZFS between substates I and II could in principle contain contributions arising from spin−spin couplings (usually on the order of 0.1 cm -1 ; compare refs and ), a ZFS of 3.8 cm -1 is clearly a consequence of spin−orbit coupling according to Pt 5d and/or MLCT character in the low-lying triplet state. ,, The importance of spin−orbit coupling for Pt(thpy)(CO)(Cl) is also evidenced by the observation of relatively intense excitation peaks at the electronic origins corresponding to absorptions from the singlet ground state to the triplet substates (Figure d).…”
Section: Assignments Comparisons and Trendsmentioning
confidence: 99%
“…2 + , with zero-field splittings of the lowest triplet state being 60, [17,18] 76, [28] and 211 cm À1 , [17,18] respectively. In contrast, complexes such as [PdA C H T U N G T R E N N U N G (thpy) 2 ] (thpy = 2-(2'-thienyl)pyridyl), [16,29] [Pd(q) 2 ] (q= 8-quinolinato), and [Pt(q) 2 ], [30] as well as [RhA C H T U N G T R E N N U N G (bpy) 3 ] 3 + [31] and [PtA C H T U N G T R E N N U N G (bpy) 2 ] 2 + [17,18] , are characterized by ZFS values significantly below 1 cm À1 . Thus, it is concluded that these complexes emit only from perturbed ligand-centered triplet states.…”
Section: [L(phenoxide)! P*a C H T U N G T R E N N U N G (Imine)] Andmentioning
confidence: 99%
“…Emission light was detected using an S20 (EMI) photomultiplier after dispersion through a colored glass cutoff filter (OG 540) and a monochromator (Jobin-Yvon, model HR1000). Microwaves were applied using the setup described previously. , The sample was mounted inside a slow-wave helix coupled to a semirigid cable in the cryostat. Microwave radiation was generated by a sweep oscillator (HP-8609B) using appropriate plug-in units (HP-86999B for 100−4000 MHz and 8691B for 1000−2000 MHz) and Hughes 1177H or Varian VZC-6961/VTC-6160/VA-615M traveling wave tube amplifiers; the amplified microwave output (∼20 W) was coupled by coaxial lines to the semirigid cable.…”
Section: Methodsmentioning
confidence: 99%
“…This paper focuses on the nature and properties of the photoexcited porphyrin triplet states in these films as studied by means of optically detected magnetic resonance (ODMR). In particular, we have applied microwave-induced fluorescence intensity measurements, i.e., fluorescence detected magnetic resonance (FDMR), in the absence of a magnetic field, to these films at 1.4 K. The ODMR technique and its theoretical background have been treated in several excellent reviews. …”
Section: Introductionmentioning
confidence: 99%